UPAYA MENINGKATKAN PEMBELAJARAN TOLAK PELURU DENGAN MENGGUNAKAN MEDIA BOLA PASIR PADA SISWA KELAS V MI NU 01 KEMANTRAN KECAMATAN KRAMAT KABUPATEN TEGAL TAHUN PELAJARAN 2013 / 2014 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to determine the extent of the increase in the learning process after using a medium shot put ball sand in class V MI NU 01 Kemantran Kramat District of Tegal. This type of research is classroom action research consisting of 2 cycles The research object is a sport that is shot put athletics. Instrument used in this research is observation sheet keterlaksanaan learning, observation sheet student motivation, student questionnaire responses and practice tests. Research said successful if students achieve mastery and learning outcomes by 76 . The results showed that the application of learning to play approach shot put with the starting target sand ball in class V MI NU 01 Kemantran Kramat District of Tegal. Student learning outcomes as a whole has increased from learning before the cycle to cycle I and cycle II. On learning before the cycle of the average value of 70.0 or 56% due to rise in the first cycle by students who completed there were 20 students, or by 64.5%, while in the second cycle increased to 31 students completed or 100% of students complete.